The reflection of teaching practice in the pedagogical education of the university teacher - Sánchez Arce, Luis Rafael; Lara Díaz, Lidia (Revista Universidad de Guayaquil, 2016)
The pedagogical training is a continuous process thot prepares and updates the university professor in the domain of the contents associated with the teaching practice, for the sake of his professional and personal development to pay tribute to the quality of the formative process of the students. It contains the field of didactic training and educational research, understood as a reflection of the teaching practice. The reflection of the teaching practice is a continuous spiral where in each phase of reflection the teacher is constantly involves in an interactive process of change and development. It takes into account the stages of action research, enhancing the reconceptualization of theory and the re- planning of new teaching activities, producing the most complete synthesis between theory and practice. The present work contributes to the pedagogical theory with the conception of the reflection of the teaching practice in the pedagogical formation of the university professor. The objective is to base the reflection of the teaching practice, as a way that favors the inclusion, from an individual and collaborative perspective, of tasks that mean a challenge for the pedagogical formation of the university professor. A guide is proposed for the reflection of the teaching practice from the action-research approach, which guides the teacher to identify their pedagogical training needs, to develop with quality the teaching- learning process in higher education, the same It was validated by experts and implemented in practice. These results are derives from a doctoral thesis defended in Pedagogical Sciences.
Keywords: pedagogical training; teaching practice; reflection on teaching practice